The Effect of pH and Temperature on Arachidonic Acid Production by Glycerol-Grown Mortierella alpina NRRL-A-10995 - Aleksei A. Mironov; Vitaly A. Nemashkalov; Nadezda N. Stepanova; Svetlana V. Kamzolova; Waldemar Rymowicz; Igor G. Morgunov (Fermentation, 2018)
Arachidonic acid (AA) has a wide range of applications in medicine, pharmacology, diet, infant nutrition, and agriculture, due to its unique biological properties. The microbiological processes involved in AA production usually require carbohydrate substrates. In this paper, we propose a method for AA production from glycerol, an inexpensive and renewable carbon substrate that is produced by the fungal strain, Mortierella alpina NRRL-A-10995. Our experimental results showed that the optimum pH values required for fungal growth and the production of lipids and AA were different and depended on the growth phase of the fungus. The AA production was shown to be extremely sensitive to acidic pH values and was completely inhibited at a pH of 3.0. The optimum temperature for AA production was 20–22 °C. Continuous cultivation of M. alpina occurred in a glycerol-containing medium, and growth limitations were implemented through the addition of nitrogen and the selection of optimal conditions (pH 6.0, 20 °C). This ensured that active AA production occurred (25.2% of lipids and 3.1% of biomass), with the product yield from the consumed glycerol being 1.6% by mass and 3.4% by energy.